Geographical accessibility to the hemodialysis centers in Ardabil, Iran - Maryam Ahmadi; Mehrnaz Mashoufi; Saeed Barzegari; Sousan Mohammadi Kebar; Saeed Hoseininia; Babak Hassanlouei; Hassan Setayeshi Nesaz; Reza Barzegari (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: Hemodialysis patients should receive hemodialysis three times per week and 140- 160 times annually. The financial and temporal costs of continuing travel to hemodialysis centers affect the type of vascular access, treatment coherence, geographical distribution and mortality of patients. Objectives: In this study, the spatial distribution and geographical accessibility of patients to the hemodialysis center and its effect on mortality and vascular access have been investigated. Patients and Methods: This descriptive-analytic study was conducted on 315 patients with chronic renal failure undergoing hemodialysis in Bou-Ali hospital of Ardabil. Accessibility to the hemodialysis center was determined by calculating the time spent from the residence to the treatment center and analyzed by ArcGIS-10. In this study, accessibility was considered in less than 10 minutes. Logistic regression was used to investigate the relationship between spatial accessibility and mortality and vascular access. To verify the correlation between different variables, Pearson's correlation, Phi and Cramer's V, and Eta tests were applied. Results: Among 315 patients, 161 patients (51.1%) were male and 277 (87.9%) patients were married. The mean age of patients was 62.7 ± 16.6 years. There were 170 illiterate patients (54%), 275 patients living in urban area (87.3%) and 132 patients as housewife (41.9%). Hospital records, showed 186 patients with arteriovenous fistula (AVF) (59%), 113 patients with central venous catheter (35.9%), since in 16 patients type of vascular access (5.1%) was not mentioned. Twenty patients (6.3%) died due to end-stage renal disease (ESRD), of which 11 were female. Additionally, eight patients (2.5%) were forced to migrate to nearby areas due to inappropriate accessibility to the hemodialysis services. The results showed a negative correlation between proximity to hemodialysis center and the prevalence of hemodialysis in women and men and the number of population in each time period. The spatial accessibility to the hemodialysis center did not correlate with the patient's mortality and type of vascular access. Conclusion: Due to the high prevalence of hemodialysis patients in the vicinity of the hemodialysis center, there is a concern that ESRD patients in rural or remote areas are not properly diagnosed or died without referral to health centers. It can be declared that one of the main reasons for the low-prevalence in remote areas is the issue of spatial accessibility. The results of this study indicated the need for further studies on the prevalence and identification of ESRD in rural areas and the causes of the disease, in order to clarify the issue's dimensions.